Adolescenti al tempo del Covid-19: una riflessione sul significato di vivere "attimi della catastrofe adolescenziale" in uno spazio-tempo negato, nella separazione corporea dal gruppo dei pari e in una relazione scolastica digitale - Maria Rita Mancaniello (Firenze University Press, 2020)
In recent months we have had clear and evident what the risks related to the pandemic were and every media on earth has highlighted the risks of SARS-CoV-2 and COVID-19. It has been talked about incessantly and with an extraordinary attention to the worst scenarios, but very little - if not some isolated voice - has highlighted the risk and the damage of the closure on the development processes of boys and girls. For boys and girls and teenagers whose social life has been completely disrupted, we know that the consequences will be there and are worrying. The emotional and cognitive fragility typical of the developmental age, deprived of the relational dimension, forced to limitations in space-time, inserted into forced dynamics within the family nucleus, subjected to the cessation and cessation of any activity proper to routines and commitments functional to growth, is now at risk of many reactions. In this context, the school experimented with an unusual form of teaching, but there may be some very important innovative elements to be taken into account